Evaluation of dual use materials science technologies issue in Ukraine – «trick or treat» - Kartuzov, Iegor (Technology audit and production reserves, 2020)
The object of this research is materials science dual-use technologies and their transfer. It is important to study the problems of transfer of dual-use technologies and related prerequisites, as well as their vital role in Ukraine, trying to understand how to fix all those in the right legal and political way, otherwise, literally, it looks like a chasing a ghost. To successfully solve this problem, one need to understand that in this case there no turnkey solutions ever exist. The complex nature of dual-use technologies and their potential for development of the economies of any countries make fundamental for both R&D and political debates. It should be noted that there has never been a clearly defined line between defense and civilian research, and that line is still rather dimmed and blurred. Dual technologies become being applied in more and more industrial sectors, from nuclear science and materials science to electronics, etc., and those are attracting increased interest from developers, policymakers and legislators. The erosion of civil and defense industrial bases and principles, as well as an avalanche growing number of problems associated with undefined dual-use functions and misuse make it difficult to distinguish between civilian and military products and platforms and complicate issues of export control and technology transfer. The concept of creating a so-called «scientific and technological depository of advanced material science technologies» by high-tech states and its’ profound significance for state’s security is also being debated. The establishment of a scientific and technical deposit is considered as a common task of national economy and security of states. A required and vitally important condition for a successful development of scientific and technological progress is the timely creation of a scientific and technical reserve of modern technologies, which provides a solid basis for new developments, state economy and military-industrial complex. The work also assesses the symbiosis of a public-private model to manage dual-use technologies in the interests of state’s security. In the course of the study, an integrated approach was employed: an analysis of world experience, as well as a retrospective and historical-evolutionary and logical approach were used to arrive the above said tasks.